The Performance of Small-Town Water Systems in the Upper West Region of Ghana - Patrick Aaniamenga Bowan; Adams Duma Amin (European Scientific Journal, ESJ, 2026)
Small-town water systems are supply systems designed mainly for residents in rural or peri-urban areas in many developing countries. This study investigated the performance of small-town water systems in the Upper West Region (UWR) of Ghana, focusing on functionality, management practices, and sustainability issues. It used an exploratory research design and combined both qualitative and quantitative methods, including surveys and interviews with water users, system operators, and officials from the Community Water and Sanitation Agency (CWSA). Results showed that although most small-town water systems were operational, they functioned below optimal levels, with overall coverage remaining under 3% across all selected districts. Major technical problems included frequent pump failures (46%), pipe leakages (22%), and unreliable power supply (16%). More than half of the system operators lacked sufficient training, and community involvement in water management was rare, as control was predominantly centralised within the CWSA. The study recommends adopting solar-powered mechanised water systems to minimise power-related disruptions, along with a comprehensive approach to water system management that encompasses technical efficiency, financial accountability, strong institutional collaboration, and inclusive community ownership to ensure sustainability and the optimal performance of small-town water systems in the UWR and similar systems in other developing countries.